The Concept of Peace in Contemporary Documents of the Magisterium Ecclesiae - Kochaniewicz, Bogusław (Studia Warmińskie, 2011)
The article deals with the notion of peace in contemporary documents of the Magisterium Ecclesiae. The analysis shows a significant development of theological reflection on the subject. John XXIII didn’t limit the Christian definition of peace to a lack of armed conflicts, but issues it from the mystery of creation. Paul VI ascribed the foundations of peace to social order (common good). John Paul II draws attention to the mystery of man (human heart as the place of peace) and presents peace as God’s gift. Benedict XVI underscores contemporary threats to peace in the world (poverty, ecologic crisis, religious freedom) and indicates ways of resolving those problems. The presented panorama of statements reveals a deepening of reflection on the subject of peace: from peace as God’s gift to peace as a task for which man is responsible; from a static definition of peace to its dynamic one. The very important task have the international institutions, too. They should resolve problems that prevent many people from fully enjoying peace.